OUR EXPERIENCE OF BILATERAL ADRENALECTOMY FOR CUSHING SYNDROME - Ulugbek B. Berkinov; Dilshod P. Sakhibayev; Jamoliddin Sh. Omonov; Mardona M. Jurayeva (Central Asian Journal of Medicine, 2023)
Purpose: to analyze the results of bilateral adrenalectomy for Cushing syndrome. Material and methods. From the analyzed 16 cases of bilateral adrenalectomy (BAE), in 14 it was performed in stages (in 11 cases with Cushing's disease (CD) after unsuccessful transsphenoidal adenomectomy (TAE), in 2 - with ectopic Cushing's syndrome (ECS), in 1 - with bilateral corticosteroma), and in two cases – simultaneously (in 2 cases with bilateral corticosteroma). The age of the patients was on average 30.14±4.13 years. In 4 cases, BAE was performed transabdominally, and in 28 cases - retroperitoneoscopically. Results. The median follow-up period was 35.5 months. After BAE, the vast majority (75%) of patients lost excess weight and achieved a BMI <25 (P < 0.001). A statistically significant improvement was also observed in arterial hypertension (from 93.75% to 50%) (P < 0.005). Before the operation, 56.25% suffered from diabetes mellitus, and after the operation - 18.5%. Acute adrenal insufficiency developed in 25% of patients. Death during the observation period was observed in 18.75% of cases. Conclusion. BAE is an effective method for treating manifestations of hypercortisolism in patients with CS. It provides good palliative treatment for CD with failed TAE and ECS. Mortality in the postoperative period is directly related to the severity of complications that develop in the preoperative period.